Design and Synthesis of Oligopeptidic Parvulin Inhibitors. (26th April 2022) - Relitti, Nicola; Prasanth Saraswati, A.; Carullo, Gabriele; Papa, Alessandro; Monti, Alessandra; Benedetti, Rosaria; Passaro, Eugenia; Brogi, Simone; Calderone, Vincenzo; Butini, Stefania; Gemma, Sandra; Altucci, Lucia; et al.
Abstract: Pin1 catalyzes the cis‐trans isomerization of pThr‐Pro or pSer‐Pro amide bonds of various proteins involved in several physio/pathological processes. In this framework, recent research activity is directed toward the identification of new selective Pin1 inhibitors. Here, we developed a set of peptide‐based Pin1 inhibitors. Direct‐binding experiments allowed the identification of the peptide‐based inhibitor 5 k (methylacetyl‐l ‐alanyl‐l ‐histidyl‐l ‐prolyl‐l ‐phenylalaninate) as a potent ligand of Pin1. Notably, 5 k binds Pin1 with higher affinity than Pin4. The comparative analysis of molecular models of Pin1 and Pin4 with the selected compound gave a rational explanation of the biochemical activity and pinpointed the chemical elements that, if opportunely modified, may further improve inhibitory potency, pharmacological properties, and selectivity of future peptide‐based parvulin inhibitors. Since 5 k showed limited cell penetration and no antiproliferative activity, it was conjugated to a polyarginine stretch (R8), known to promote cell penetration of peptides, to obtain the R8–5 k derivative, which displayed antiproliferative effects on cancer cell lines over non‐tumor cells. The effect of R8 on cell proliferation was also investigated. This work warrants caution about applying the R8 strategy in the development of cell‐penetrating antiproliferative peptides, as it is not inert. Abstract : Pinning down potency and selectivity : Direct‐binding experiments allowed the identification of methylacetyl‐l ‐alanyl‐l ‐histidyl‐l ‐prolyl‐l ‐phenylalaninate (5 k ) as a potent Pin1 ligand that binds Pin1 with higher affinity than Pin4. Comparative analysis of molecular models of Pin1 and Pin4 with the selected compound explained the biochemical activity and pinpointed the chemical elements that may further improve the potency and selectivity of future peptide‐based parvulin inhibitors.